2015
DOI: 10.1002/cbin.10480
|View full text |Cite
|
Sign up to set email alerts
|

Radio‐modifying potential of Saraca indica against ionizing radiation: an in vitro study using Chinese hamster lung fibroblast (V79) cells

Abstract: This study demonstrated the radioprotective efficacy of extracts prepared from stem bark of Saraca indica (SI) against X-rays induced cellular damage, which was evaluated by a battery of cytotoxicity, genotoxicity, apoptotic, and biochemical assays using Chinese hamster fibroblast (V79) cells. Cell viability and surviving fraction were increased significantly when V79 cells were preconditioned with optimal concentration of hydroalcoholic extract (HE; 50 μg/mL) of SI for 2 h prior exposure to X-rays. Radiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…When comparing with the literature, it is observed that both extracts are promising in the inhibition of lipid peroxidation since 50 µg/mL of hydroalcoholic extract produced from the bark of the stem of Saraca indica , which has antioxidant activity and the ability to reduce cytotoxicity and genotoxicity induced by irradiation with X-rays, was able to reduce MDA concentration after X-rays exposure by 1,5-fold ( Das et al., 2015 ), and methanolic extracts of BvFV and BvFIX at the same concentration reduced MDA by approximately 4 and 2.5-fold, respectively, after induction of oxidative stress. A study by Perez et al., 2009, showed that the lifespan of mice lacking the sod1 gene was reduced compared to wild-type mice.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…When comparing with the literature, it is observed that both extracts are promising in the inhibition of lipid peroxidation since 50 µg/mL of hydroalcoholic extract produced from the bark of the stem of Saraca indica , which has antioxidant activity and the ability to reduce cytotoxicity and genotoxicity induced by irradiation with X-rays, was able to reduce MDA concentration after X-rays exposure by 1,5-fold ( Das et al., 2015 ), and methanolic extracts of BvFV and BvFIX at the same concentration reduced MDA by approximately 4 and 2.5-fold, respectively, after induction of oxidative stress. A study by Perez et al., 2009, showed that the lifespan of mice lacking the sod1 gene was reduced compared to wild-type mice.…”
Section: Discussionmentioning
confidence: 96%
“…The BvFIX extract increased in SOD activity, which was dose-dependent compared to enzyme activity in cells that did not undergo oxidative stress ( Figure 6 ). When comparing results obtained with 50 µg/mL of hydroalcoholic extract produced from the bark of Saraca indica , which was able to increase SOD activity by 1.3-fold after exposure to X-rays ( Das et al., 2015 ), BvFIX metabolites can be considered promising in reducing premature skin aging, since the methanolic fraction of BvFIX extract at same concentration increased SOD activity by 3.6-fold after induction of oxidative stress. H 2 O 2 produced by SOD activity is broken down into water and oxygen by catalase ( Pérez et al., 2009 ; Kim, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations